(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate differences in dose distribution and the physical characteristics of intensity-modulated radiation therapy (IMRT) plans for patients with hypopharyngeal-esophageal cancer using two CT-to-relative electron density conversion datasets, Nghean2022 and Rocsboard02. Subjects and methods: This retrospective study included simulation CT data from 23 patients with hypopharyngeal-esophageal cancer whose IMRT plans had originally been generated using the Nghean2022 HU-RED dataset. All plans were recalculated in Monaco version 5.11.03 using the Rocsboard02 dataset while keeping the original treatment parameters unchanged. The evaluated parameters included target coverage (Q), conformity index (CI), homogeneity index (HI), absorbed doses to organs at risk (OARs), monitor units (MU), and beam-on time. Results: The two HU-RED datasets produced comparable dose distributions for the treatment volumes. Compared with Nghean2022, Rocsboard02 showed a tendency to reduce MU and beam-on time by approximately 1.4%. Differences in absorbed doses to OARs, including the spinal cord, parotid glands, heart, and lungs, were minimal and generally below 2%. No statistically significant differences were observed between the two datasets for any of the evaluated parameters (p > 0.05). Conclusion: The use of either the Rocsboard02 or Nghean2022 HU-RED dataset for IMRT planning in patients with hypopharyngeal-esophageal cancer resulted in comparable dose distribution quality and physical treatment-plan characteristics.